Microbial Secretion Platform for 3‐Hydroxybutyrate Oligomer and Its End‐Capped Forms Using Chain Transfer Reaction‐Mediated Polyhydroxyalkanoate Synthases. Issue 12 (21st November 2019) - Miyahara, Yuki; Hiroe, Ayaka; Tsuge, Takeharu; Taguchi, Seiichi
Abstract: The biodegradable polyester 3‐hydroxybutyrate (3HB) polymer [P(3HB)] is intracellularly synthesized and accumulated in recombinant Escherichia coli . In this study, native polyhydroxyalkanoate (PHA) synthases are used to attempt to microbially secrete 3HB homo‐oligomers (3HBOs), which are widely distributed in nature as physiologically active substances. High secretory production is observed, especially for the two PHA synthases from Aeromonas caviae and Bacillus cereus YB4. Surprisingly, an ethyl ester at the carboxy terminus (ethyl ester form) of 3HBOs is identified for most of the PHA synthases tested. Next, 3HBOs with a functional carboxyl group (carboxyl form of 3HBO) are obtained by using the alcohol dehydrogenase gene ( adhE )‐deficient mutant strain, suggesting that the endogenous ethanol produced in E. coli acts as a chain transfer (CT) agent in the generation of 3HBOs. Furthermore, an in vitro polymerization assay reveals that CT agents such as ethanol and free 3HB are involved in the generation of ethyl ester and carboxyl form of 3HBO, respectively. The microbial platform established herein allows the secretion of 3HBOs with desirable end structures by supplementation with various CT agents. The obtained 3HBOs and their end‐capped forms may be used as physiologically active substances and building blocks for polymeric materials. Abstract : 3‐hydroxybutyrate (3HB) oligomers with an enantiopure of ( R )‐form are well known compounds as physiologically active substances in nature. In this study, the microbial secretion system for the 3HB oligomers (3HBOs) are developed by using native polyhydroxyalkanoate (PHA) synthases. 3HBOs end‐capped with chain transfer (CT) agents are produced via chain transfer reaction‐mediated PHA synthases. The secreted 3HBOs could be used as not only physiologically active substances but also building blocks for polymeric materials. This article is part of an AFOB (Asian Federation of Biotechnology) Special issue. To learn more about the AFOB visit www.afob.org.